2010
DOI: 10.1016/j.juro.2010.03.083
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Evaluation of Parental Decision Making Factors for Vesicoureteral Reflux Management in Children

Abstract: Data indicate that the parents of our patients highly value the opinion of the pediatric urologist when choosing treatment for their children with vesicoureteral reflux. Despite social changes the physician-parental relationship remains critical. Differences in parental decision making may be linked to associations between race and income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…29 Similarly, in a recent survey of parents making decisions about treatment for children with vesicoureteral reflux, more than 90% considered the urologist’s opinion to be very or extremely important. 51 …”
Section: Resultsmentioning
confidence: 99%
“…29 Similarly, in a recent survey of parents making decisions about treatment for children with vesicoureteral reflux, more than 90% considered the urologist’s opinion to be very or extremely important. 51 …”
Section: Resultsmentioning
confidence: 99%
“…A recent study on the treatment patterns of reflux showed that 80% of parents of patients with moderately severe VUR chose endoscopic injection when given information on each of the treatment options [57]. Both the opinion of the pediatric urologist and the individual hospital at which the patient seeks treatment influenced the procedure performed [58, 59]. …”
Section: Discussionmentioning
confidence: 99%
“…Education and counseling play an important role in parental preferences of VUR management, with the pediatric urologist's opinion often cited as the chief determining factor. 28,29 VURx is applicable only to children diagnosed with primary VUR before 2 years of age.…”
Section: A N U S C R I P Tmentioning
confidence: 99%